Grammatical metaphor: Exploring the semogenic power of the language - Behrooz Azabdaftari (Iranian Journal of Language Teaching Research, 2015)
This paper seeks to elaborate on the notion of 'grammatical metaphor' intended by M. A. K. Halliday (1983) in his Functional Systemic Linguistics (FSL). 'Metaphor' in linguistic parlance is 'a process of mapping between two different conceptual domains - the source domain and the target domain'. Halliday draws on this definition of lexical metaphor and applies the concept to syntactical structures, a gimmick whereby a particular grammatical structure is converted into another structure while the original meaning is preserved. A good many examples are supplied to illustrate the points in case. Also, this paper deals with different kinds of metaphors. The key argument in this paper centers on the methodology of teaching writing to English majors in the author's English composition classes which we applied some years ago in the English program in the University of Tabriz. The claim we make is that the methodology of teaching writing which we used in our composition classes was indeed the practical realization of the tenets of grammatical metaphor intended by Halliday in his FSL.